A systematic review and meta-analysis of vertical transmission route of HIV in Ethiopia - Aklilu Endalamaw (BMC Infectious Diseases, 2018)
Abstract Background The burden of mother-to-child transmission rate of HIV is high and risk factors are common in Ethiopia. This systematic review and meta-analysis intended to provide the pooled estimation of mother-to-child transmission rate and its risk factors in Ethiopia. Methods We searched PubMed, Google Scholar, EMBASE and Web of Science electronic databases for all available references. We included observational studies including case-control, cohort, and cross-sectional studies. The search was further limited to studies conducted in Ethiopia and publish in English. Heterogeneity was checked using the I2 statistic. Egger’s test and the funnel plot were used to assess publication bias. A meta-analysis using a weighted inverse variance random-effects model was performed. Results A total of 18 studies with 6253 individuals were included in this systematic review and meta-analysis. Of these, 14 studies with 4624 individuals were used to estimate the prevalence. The estimated pooled prevalence of mother-to-child transmission of HIV was 11.4% (95% CI = 9.1–13.7). The pooled adjusted odds ratio (AOR) of mother-to-child transmission of HIV for the infants from rural area was 3.8 (95% CI = 1.4 to 6.3), infants delivered at home was 3.2 (95% CI = 1.2 to 5.2), infant didn’t take antiretroviral prophylaxis was 5.8 (95% CI = 1.5 to 10.3), mother didn’t take antiretroviral prophylaxis was 6.1 (95% CI = 2.5 to 9.6), mothers didn’t receive PMTCT intervention was 5.1 (95% CI = 1.6, 8.6), and on mixed feeding was 4.3 (95% CI = 1.8 to 6.7). Conclusions This systematic review and meta-analysis showed that mother-to-child transmission rate of HIV was high in Ethiopia. Being from the rural residence, home delivery, not taking antiretroviral prophylaxis, the absence of PMTCT intervention, and mixed infant feeding practices increased the risk of HIV transmission. Trial registration It is registered in the Prospero database: (PROSPERO 2017: CRD42017078232).